Design of mannosylated oral amphotericin B nanoformulation: efficacy and safety in visceral leishmaniasis. (31st October 2018) - Sarwar, Hafiz Shoaib; Sohail, Muhammad Farhan; Saljoughian, Noushin; Rehman, Anees Ur; Akhtar, Sohail; Nadhman, Akhtar; Yasinzai, Masoom; Gendelman, Howard E.; Satoskar, Abhay R.; Shahnaz, Gul
Abstract: The aim of this study was to evaluate mannose-anchored thiolated chitosan (MTC) based nanocarriers (NCs) for enhanced permeability, improved oral bioavailability and anti-parasitic potential of amphotericin B (AmB). Transgenic Leishmania donovani parasites expressing red fluorescent protein DsRed2 and imaging-flow cytometry was used to investigate parasitic burdens inside bone marrow-derived macrophages ex vivo. Cytokine estimation revealed that MTC nanocarriers activated the macrophages to impart an explicit immune response by higher production of TNF-α and IL-12 as compared to control. Cells treated with MTC NCs showed a significantly higher magnitude of nitrite and propidium iodide (PI) fluorescence intensity in contrast to cells treated with AmB. Concerning to apparent permeability coefficient ( P app ) results, the MTC NCs formulation displayed more specific permeation across the Caco-2 cell monolayer as compared to AmB. The half-life of MTC NCs was about 3.3-fold persistent than oral AmB used as positive control. Also, t oral bioavailability of AmB was increased to 6.4-fold for MTC NCs compared to AmB for positive control. Acute oral evaluation indicated that MTC NCs were significantly less toxic compared to the AmB. Based on these findings, MTC NCs seems to be promising for significant oral absorption and improved oral bioavailability of AmB in leishmaniasis chemotherapy. Graphical Abstract: UF0001